Circ_0010235 facilitates lung cancer development and immune escape by regulating miR‐636/PDL1 axis. Issue 7 (15th February 2022) - Zhao, Jixing; Yan, Wu; Huang, Wencong; Li, Yongsheng
Abstract: Background: Circular RNAs (circRNAs) are a class of important regulators in various human cancers, including lung cancer. Here, we aimed to investigate the role of circ_0010235 in lung cancer. Methods: The expression of circ_0010235, microRNA‐636 (miR‐636) and PDL1 was measured by quantitative real‐time PCR (qRT‐PCR). Cell proliferation was evaluated by CCK‐8, colony formation, and 5‐ethynyl‐2′‐deoxyuridine (EdU) assays. Cell apoptosis was detected by flow cytometry. Cell invasion was assessed by transwell assay. All protein levels were determined by western blot assay. In order to detect the roles of circ_0010235 in immune escape, lung cancer cells were cocultured with peripheral blood mononuclear cells (PBMCs) or cytokine‐induced killer (CIK) cells in vitro. The relationship between miR‐636 and circ_0010235 or PDL1 was verified by dual‐luciferase reporter assay and RNA pulldown assay. Immunohistochemistry (IHC) analysis was used to detect Ki67 and programmed death‐ligand 1 (PDL1) expression. A xenograft tumor model was established to verify the function of circ_0010235 in vivo. Results: Circ_0010235 was overexpressed in lung cancer. Circ_0010235 knockdown inhibited proliferation, invasion and immune escape and promoted apoptosis of lung cancer cells. MiR‐636 was a target of circ_0010235, and miR‐636 inhibition reversed the effects of circ_0010235 knockdown in lung cancer cells. PDL1 was a direct target of miR‐636, and miR‐636 suppressed the proliferation and invasion and increased apoptosis and antitumor immunity in lung cancer cells by downregulating PDL1. Moreover, circ_0010235 positively regulated PDL1 expression by sponging miR‐636. Additionally, circ_0010235 knockdown hampered tumorigenesis in vivo. Conclusion: Circ_0010235 knockdown inhibited lung cancer progression and increased antitumor immunity by regulating the miR‐636/PDL1 axis. Abstract : Circ_0010235 promotes lung cancer cell proliferation, invasion, immune escape and tumor growth while it reduces cell apoptosis by regulating miR‐636/PDL1 axis, thereby accelerating lung cancer development.